The Role of Islamic Religious Education in Responding to the Moral Crisis: Internalizing the Value of Trust and Honesty as an Anti-Corruption Effort - Reka Annisa Sahera; Jafar Ahmad; Najmi Sarah, RZ; Muhammad Khairi; Muhammad Fadlan (Jurnal Recoms, 2026)
This research aims to examine the role of Islamic Religious Education (PAI) in addressing moral crises by internalizing the values of trust and honesty as an anti-corruption effort. The background of this research is the limited application of moral values in students' lives and the lack of optimal integration of anti-corruption education into PAI learning. This research uses a qualitative approach with a literature review type that focuses on the analysis of previous research in the form of journals and scientific articles in the last five years. Data collection techniques are carried out through documentation studies, while data analysis uses descriptive techniques by studying, grouping, and interpreting findings from various studies. The results of the study show that PAI has a strategic role in instilling the value of trust and honesty, but its implementation still faces obstacles such as learning approaches that tend to be theoretical, a lack of habituation, and the systematic integration of anti-corruption education in the curriculum. Therefore, it is necessary to strengthen a more contextual and sustainable learning strategy so that these values can be internalized in real life in students' lives.